Description of an Integrated and Dynamic System to Efficiently Deal With a Raging COVID-19 Pandemic Peak - Agnoletti, Vanni; Gamberini, Emiliano; Circelli, Alessandro; Martino, Costanza; Santonastaso, Domenico Pietro; Bolondi, Giuliano; Bastoni, Giorgia; Spiga, Martina; Ceccarelli, Paola; Montaguti, Luca; Catena, Fausto; Poletti, Venerino; et al. (Frontiers in Medicine, 2022)
Background This study aimed to describe an innovative and functional method to deal with the increased COVID-19 pandemic-related intensive care unit bed requirements. Methods We described the emergency creation of an integrated system of internistic ward, step-down unit, and intensive care unit, physically located in reciprocal vicinity on the same floor. The run was carried out under the control of single intensive care staff, through sharing clinical protocols and informatics systems, and following single director supervision. The intention was to create a dynamic and flexible system, allowing for rapid and fluid patient admission/discharge, depending on the requirements due to the third Italian peak of the COVID-19 pandemic in March 2021. Results This study involved 142 COVID-19 patients and 66 non-COVID-19 patients who were admitted; no critical patient was left unadmitted and no COVID-19 severe patients referring to our center had to be redirected to other hospitals due to bed saturation. This system allowed shorter hospital length-of-stay in general wards (5.9 ± 4 days) than in other internistic COVID-19 wards and overall mortality in line with those reported in literature despite the peak raging. Conclusion This case report showed the feasibility and the efficiency of this dynamic model of hospital rearrangement to deal with COVID-19 pandemic peaks.